RETHINKING SECTORAL TYPOLOGIES: A CLASSIFICATION OF ACTIVITY ACCORDING TO KNOWLEDGE AND TECHNOLOGICAL INTENSITY (INMR - Innovation & Management Review, 2017)
This article aims to integrate and adapt two classifications of economic activity from the Organization for Economic Cooperation and Development(OECD) and the Statistical Office of the European Commission (Eurostat) into a Brazilian context and contemporary studies of economicdevelopment. The classification that emerges, called the “Classification of economic activity according to technology and knowledge intensity”,results in (i) valuing the criteria that deals with the present and future factors of competitiveness, such as technology and knowledge, science andinnovation, and transversability and dissemination of information; (ii) overcoming the old dichotomy between manufacturing and services with anew but flexible and gradual classification, ranging from more high-tech and knowledge-intensive activities to low-tech, less knowledge-intensiveactivities.